IMPLEMENTATION OF TAX COLLECTION TO INCREASE INDIVIDUAL INCOME TAX REVENUE - Endang Susilawati; Asep Mulyana (Accounting Research Journal, 2023)
This study aims to determine the implementation of tax collection to increase personal income tax revenue whether there is a big effect after billing individuals. domestic private person. Taxes have a very large role in generating domestic cash receipts in order to realize continuity and increase in national development. The method used in this research is a quantitative method with a descriptive approach and the data used is secondary data. The results of the study show that partially Billing does not have a significant effect on Individual Income Tax Receipts.